Moral Panics and Punctuated Equilibrium in Public Policy: An Analysis of the Criminal Justice Policy Agenda in Britain. - Jennings, Will; Farrall, Stephen; Gray, Emily; Hay, Colin (Policy Studies Journal, 2020)
How and when issues are elevated onto the political agenda is a perennial question in the study of public policy. This article considers how moral panics contribute to punctuated equilibrium in public policy by drawing together broader societal anxieties or fears and thereby precipitating or accelerating changes in the dominant set of issue frames. In so doing they create opportunities for policy entrepreneurs to disrupt the existing policy consensus. In a test of this theory, we assess the factors behind the rise of crime on the policy agenda in Britain between 1960 and 2010. We adopt an integrative mixed‐methods approach, drawing upon a combination of qualitative and quantitative data. This enables us to analyze the rise of crime as a policy problem, the breakdown of the political‐institutional consensus on crime, the moral panic that followed the murder of the toddler James Bulger in 1993, the emergence of new issue frames around crime and social/moral decay more broadly, and how—in combination—these contributed to an escalation of political rhetoric and action on crime, led by policy entrepreneurs in the Labour and Conservative parties.